A Delamination Strategy for Thinly Layered Defect‐Free High‐Mobility Black Phosphorus Flakes. Issue 17 (15th March 2018) - Yang, Sheng; Zhang, Ke; Ricciardulli, Antonio Gaetano; Zhang, Panpan; Liao, Zhongquan; Lohe, Martin R.; Zschech, Ehrenfried; Blom, Paul W. M.; Pisula, Wojciech; Müllen, Klaus; Feng, Xinliang
Abstract: Extraordinary electronic and photonic features render black phosphorus (BP) an important material for the development of novel electronics and optoelectronics. Despite recent progress in the preparation of thinly layered BP flakes, scalable synthesis of large‐size, pristine BP flakes remains a major challenge. An electrochemical delamination strategy is demonstrated that involves intercalation of diverse cations in non‐aqueous electrolytes, thereby peeling off bulk BP crystals into defect‐free flakes comprising only a few layers. The interplay between tetra‐ n ‐butylammonium cations and bisulfate anions promotes a high exfoliation yield up to 78 % and large BP flakes up to 20.6 μm. Bottom‐gate and bottom‐contact field‐effect transistors, comprising single BP flakes only a few layers thick, exhibit a high hole mobility of 252±18 cm 2 V −1 s −1 and a remarkable on/off ratio of (1.2±0.15)×10 5 at 143 K under vacuum. This efficient and scalable delamination method holds great promise for development of BP‐based composites and optoelectronic devices. Abstract : Defect‐free black phosphorus (BP) flakes were prepared on a macroscopic scale by a simple and scalable exfoliation method. Delaminated and mechanically exfoliated BP flakes present comparable electronic properties. This efficient and scalable method holds promise for development of BP‐based composites and optoelectronic devices.